Neuro-imaging in Somatoform Disorders: A review - Atmaca, Murad (Turkiye Sinir ve Ruh Sagligi Dernegi, 2012)
Neuro-imaging in Somatoform Disorders: A review As other psychiatic disorders, the etiopathogenesis of somatoform disorders is obscure. However, it occurs by the combination of psyhosocial and biological factors. Our knowledge on biological basics of somatoform disorders is obviously limited. When compared to other psychiatric disorders, somatoform disorders are in infancy period in regard to neuroradiologic data. In this paper, we reviewed the structural and functional neuroimaging data in DSM-IV-TR somatoform disorders. The studies on conversion disorder revealed functional changes in cortical areas, and both structural and functional alterations in subcortical regions such as thalamus and basal ganglia. Neuro-imaging findings determined in hypochondriasis such as smaller orbito-frontal cortex and pituitary and larger thalamus provide an important contribution to establish that hypochondriasis is one of obsessive-compulsive spectrum disorders beyond possible role on the pathophysiology of the disorder. The findings coming from the investigations on somatization disorder are larger caudate nucleus, smaller amygdala and hypoperfusion in non-dominant hemisphere. In body dysmorphic disorder, it was reported abnormal activation in the inferior frontal gyrus and amygdala, assimetry of caudate nucleus, increased white matter, smaller anterior cingulate cortex and orbitofrontal cortex volumes. In the chronic pain conditions with or without somatoform pain, it was demonstrated to increase D2 receptor affinity and to decrease grey matter volumes, as in fibromyalgia.
Keywords: Somatoform; somatization; conversion; magnetic resonance; spectroscopy